Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja pada Kantor Kecamatan Bojong Gede Kabupaten Bogor - Mochamad David Andreas Priatna; Rani Kurniasari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Employee performance is very important to involve the company's progress, good performance involves good contributions. Leadership style is a person's ability to influence and provide guidance to individuals to achieve their goals. Work discipline is reflection and respect for each other, compliance with written and verbal rules, readiness to face the consequences of any violation of the responsibilities and authority assigned to them. This research aims to determine the influence of leadership style and work discipline on performance. This research also uses a quantitative statistical approach using the SPSS 25 application. Data collection techniques are questionnaires, observation and literature study. The research population was 45 and the sampling technique used saturation. The results of this research are that there is a partial influence of the leadership style variable on performance with a calculated T value of 3,503>2.017. There is a partial influence of the Work Discipline variable with a calculated T value of 2,186>2.017. There is a simultaneous influence with the leadership style and work discipline variables on performance with a calculated F value of 10.244>3.21